Preference in powerpoint presentation among first-year medical students: A nationwide online cross-sectional survey - Himel Mondal; Shaikat Mondal; Sharada Mayee Swain (Wolters Kluwer Medknow Publications, 2024)
Background and Aim: PowerPoint slides are commonly used to project class materials such as text and images, offering enhanced visualaids. However, preference among medical students has not been thoroughly explored. Therefore, we conducted this study to investigate the preference in PowerPoint slides and its delivery method among medical students. Materials and Methods: We conducted a cross-sectional observational study involving undergraduate medical students studying in any Indian medical college. An online survey was administered using a pre-tested questionnaire distributed through the Google Forms platform. The survey items encompassed overall preference, content and arrangement preference, diagram preference, text preference, access preference, and ambiance preference. Results: The study included 728 students, with a gender distribution of 66.35% boys and 33.65% girls. PowerPoint presentations were found helpful by 68.27% of students, while 53.85% found the class enjoyable. Preferences included major points in slides (81.73%), large text size (86.54%), and different colored headings (87.5%). Images aided understanding (85.58%), animations made the class interesting (92.31%), and access to slides before and after class was preferred. Students liked a dimly lit hall, teacher facing them, and the use of a laser pointer or stick. Font preferences were blue (45%) and black for body text (57%), with Verdana as the preferred font (89%). A white background was favored by 86% of students, with 67% preferring a clear background and 33% a designed or textured background. Conclusion: Medical students prefer PowerPoint slides with clear organization, large text, and visual aids such as images and animations. Accessibility to slides before and after classes is valued, and a conducive learning environment includes proper lighting, teacher-student interaction, and effective presentation tools. These insights can guide educators in creating more engaging and effective presentations for medical students.